The lessons of the pandemic (COVID-19): the impact of changing the value orientation of the population on marketing strategies for tourism development - Borbasova, Z.N.; Ulakov, S.N.; Ulakov, N.S. (BUKETOV BUSINESS REVIEW, 2023)
Object: to consider the impact of the COVID-19 pandemic on the population’s value system and analyze changes in value orientations that were considered important in recent decades. The main goal of the article is to propose marketing strategies that correspond to the directions of development in the “post-pandemic” period, taking into account the “lessons of the pandemic” for the tourism industry. Methods: during the study, methods of synthesis and analysis were used, including systematic and integrated approaches (general scientific and special). Findings: the value orientations of the population and transformation in the field of tourism are comprehensively considered. They are analyzed in connection with the consequences of the “corona crisis”, as well as the impact on the development of human potential and the possibility of its positive direction in terms of changing universal human values. Based on a scientific approach, five lessons from the pandemic are identified and, on their basis, directions for the development of a marketing strategy for the tourism industry are proposed. Conclusions: the scientific novelty of the work lies in the fact that the authors were among the first to systematically study some of the positive aspects of the “corona crisis” that influenced the development of society, and presented them in the form of five lessons from the pandemic, which makes the article especially relevant in a practical sense. Directions for the development of a marketing strategy for the tourism industry in the “post-pandemic” period are proposed in accordance with the concept of conscious consumption marketing.